The Model of the Elderly Schoot The Model of the Elderly School Administration of Local Government in Nakhon Si Thammarat - Jaratep, Gaevalin; Sumato, Phramaha Supot; Somkhaoyai, Teeraphong; Onkong, Samit (Academic MCU Buriram Journal, 2021)
This research aimed 1) to study the administrative condition of the elderly school administration of local administrative government, 2) to explore the management model of the elderly school of the local administrative government, and 3) to propose the management model of the elderly school of the local administrative government. This study was conducted using a qualitative research method with data collected by in-depth interviews with 15 informants from related parties, 3 informants who provided in-depth data, group discussion by 7experts The research result finds that: 1.The school management condition of the elderly school administration of local government consisted of 4 areas of management: 1) activities, 2) committee, 3) fund, and 4) associate network operated by all sectors in brainstorming, co-creation to operate in learning management to make the elderly happy with the skills to take a self-care leading to better quality of life. 2. The management model of the elderly school administration of local government in Nakhon Si Thammarat, consisted of 4 aspects: 1) activities, including (1) activities held within the school to enhance 3 subjects, life, professional, and academic, (2) activities held outside the school, religious activities, volunteering, service; 2) board of committees including (1) the Advisory Committee, (2) the Executive Committee; 3) the fund including (1) the fund source on one own, from state and private sectors, donation, products of elderly students, (2) how to access the fund source, (3) the use of fund sources, 4) the party network consisting of (1) social associate networking party within the group, (2) associate party to the external corporate network. 3. Regarding the experts scrutinized the management model of the elderly school administration of local government in Nakhon Si Thammarat, it was found that the model was appropriate, possibility, advantageous, and practical.